A comparison of methods to estimate groundwater recharge from bare soil based on data observed by a large‐scale lysimeter. Issue 13 (5th May 2020) - Zhang, Zaiyong; Wang, Wenke; Gong, Chengcheng; Zhang, Ming
Abstract: Effectively estimating groundwater recharge is critical to manage water resources, especially in arid and semi‐arid regions as impacted by intensive human activities and climate changes. Rare insights have been gained into groundwater recharge since direct observation is hard to carry out. Although several methods are currently available to estimate groundwater recharge, the estimated results may cover noticeable bias. The behaviours of different methods based on different conceptual frameworks and exhibiting different levels of complexity should be examined to estimate actual groundwater recharge. This study aims to assess the performance of four common methods to estimate groundwater recharge. For this end, large‐scale lysimeters equipped with soil water content sensors and water table sensors were set up at a research site established in Guanzhong Basin of China. The data achieved by 1‐year observation were employed to compare four estimation methods. As revealed from the results, the following findings are drawn. (a) Groundwater level fluctuation (GLF) method is simple, whereas its accuracy is determined by specific yield, and adopting a water balance method to estimate specific yield can considerably enhance the accuracy of GLF. (b) The calibrated numerical model can obtain the optimal result compared with the other methods, whereas long‐term observation data are required for parameter calibration. (c) In the water balance method, the maximum entropy production (MEP) model and a practical method (estimating evaporation between two rainfall events) were used to calculate evaporation. As indicated by the results, water balance method combined with MEP is capable of obtaining more reliable results of groundwater recharge compared with the practical method. (d) With an analytical model based on linearized Richards' equation, accurate results can be achieved. What is more, the analytical model only needs the measurement of soil moisture near the surface. The limitation of this method is that it is difficult to determine the maximal water flux. The mentioned findings are of critical implications to the management and sustainable development of groundwater. Abstract : Multiple methods have been compared in the identification of groundwater recharge Physically‐based model is the optimal choice to estimate groundwater recharge An analytical model not required for calibration illustrated an acceptable performance in the estimation of groundwater recharge